Corporate Social Responsibility (CSR) dan Profitabilitas: Pengaruh aspek ekonomi, lingkungan, dan social pada Perusahaan Manufaktur - Endrawati, Endrawati; Santi, Elfitri; Putri, Velli Maita (Akuntansi dan Manajemen, 2024)
This study was conducted to determine how the influence of Corporate Social Responsibility (CSR) disclosure on profitability. This research uses a quantitative approach method. The data analysis technique used in this research is panel data regression analysis technique and the data is processed using STATA software version 16. Disclosure of economic, environmental, and social aspects of CSR as independent variables, company size, and sub-sector as control variables and profitability projected by Return on Asset (ROA) and Net Profit Margin (NPM) as dependent variables. This research was conducted in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2021. The sample selection in this study used purposive sampling method and obtained 29 sample companies. The results of this study indicate that the disclosure of CSR in economic, environmental, and social aspects does not have a significant effect on ROA. Likewise, CSR disclosure of environmental and social aspects. The larger the size ot the firm, the higher CSR disclosure carried out by the company.